Physical fitness interventions for primary school students with special educational needs: a bibliometric analysis of global trends in inclusive education (1964–2025) - Ranjanie Karunamoorthy; Khairul Farhah Khairuddin; Nur Shakila Mazalan (Institute of Advanced Engineering and Science, 2026)
Physical fitness is a critical determinant of health, development, and well-being for children with special educational needs (SEN), yet their participation in physical activity remains limited due to physical, social, and institutional barriers. Although adapted physical activity (APA) interventions have been widely investigated, the global evolution of research on physical fitness among children with disabilities has not been systematically mapped. This study conducts a bibliometric analysis of Scopus-indexed publications from 1964 to 2025 focusing on school-aged children (approximately 5-12 years) with physical, intellectual, sensory, and developmental disabilities. Studies unrelated to physical fitness or exercise outcomes were excluded. A total of 536 documents were analyzed using Scopus Analyzer, Microsoft Excel, and VOSviewer to examine publication trends, document types, country productivity, authorship patterns, collaboration networks, keyword co-occurrence, and bibliographic coupling. The inclusion of 2025 records reflect early-access indexing at the time of retrieval. Results indicate substantial growth in research output, particularly after 2016. Research is predominantly concentrated in high-income Western countries. Established themes center on rehabilitation and motor performance, while emerging topics include inclusion, adaptive sports, and psychosocial outcomes. Findings should be interpreted cautiously due to reliance on a single database and English-language dominance.